Assessing flood resilience of urban drainage system based on a 'do-nothing' benchmark. (15th June 2021) - Wang, Mingming; Fang, Yuting; Sweetapple, Chris
Abstract: To deal with the threat of urban flooding, it is necessary to assess the flood resilience of urban drainage systems at the planning and design stage. This study proposes a system resilience assessment methodology based on a 'do-nothing' benchmark. In this new benchmark, the number of flooded nodes used in computation of mean flood duration in the system is that observed under a 'do-nothing' scenario (i.e. with no intervention), irrespective of the scenario under evaluation. This methodology is demonstrated using a case study in Chizhou city, China, a simple stormwater drainage network with seven subcatchments. Schemes of interventions (with distributed storage tanks) that aim to mitigate flooding are then produced by zero-one integer programming and schemes sampling. The results show that the proposed method can compute the mean flood duration and system resilience reasonably and helps identify effective intervention schemes. Compared with traditional methods, this resilience assessment method based on a 'do-nothing' scenario can correctly indicate the change in trend of system resilience provided by different schemes, and aids understanding of different interventions to improve system resilience to urban flooding. This study also provides a new way to test different interventions and to explore which provide the greatest improvement in system resilience. Highlights: A system resilience assessment methodology based on a 'do-nothing' benchmark is presented. The number of flooded nodes in the system is determined on a 'do-nothing' basis. Schemes of interventions are produced by zero-one integer programming and schemes sampling. The method will help understanding of different interventions and improve system resilience.